Star wars. Rogue One : graphic novel adaptation - Ferrari, Alessandro (Alessandro Q.) (San Diego, CA : IDW Pub., a division of Idea and Design Works, LLC, 2017)
"The Death Star, the Empire's ultimate weapon, is nearing completion, and the Rebel Alliance may be doomed. Enter Jyn Erso, daughter of the Death Star's reluctant creator, who desperately seeks to save her father from Imperial control. On her quest, she'll join forces with Rebel spy Cassian Andor, reprogrammed Imperial droid K-2SO, and other supporters of the Rebel cause, only to discover that their goals may differ crucially from her own. It all culminates in a ... showdown on the tropical planet Scarif, with Jyn and her friends attempting to steal the Death Star's plans and keep hope for the Rebellion alive"--Back cover.
"Based on a story by John Knoll and Gary Whitta ; screenplay written by Chris Weitz and Tony Gilroy"--Colophon.
Cover title: Rogue One
Graphic novelization of the motion picture Rogue One.
Subtitle from front cover.
3.8
3-6
Keywords: Good and evil -- Comic books, strips, etc. -- Juvenile fiction; Interplanetary voyages -- Comic books, strips, etc. -- Juvenile fiction; Space warfare -- Comic books, strips, etc. -- Juvenile fiction; Star Wars fiction; Good and evil -- Fiction; Interplanetary voyages -- Fiction; Space warfare -- Fiction; Star Wars fiction; Good and evil -- Comic books, strips, etc. -- Fiction; Interplanetary voyages -- Comic books, strips, etc. -- Fiction; Space warfare -- Comic books, strips, etc. -- Fiction; Star Wars fiction; Comics adaptations; Graphic novels; Science fiction comics